Design, Synthesis, and Biological Evaluation of Novel Mitochondria-Targeting Fluorescent Phenothiazine Derivatives as Potential Anticancer Agents - Ning, Xiaojun; Chai, Fangyuan; Chen, Tao; Yan, Ke; Min, Shuang; Guo, Lijian; Jia, Aiting; Zhang, Lu; Jiang, Dan; Du, Linli; Gao, Tao (Synlett, 2024)
In this research, we synthesized a novel mitochondrial-targeted antitumor lead compound named phenolthiazide-4C-Pvi (PCP) by modifying a phenothiazine with 3-(2-pyridin-4-ylvinyl)-1H-indole (Pvi) as a mitochondrial-targeted fluorescent cargo. Our preliminary findings indicated that PCP exhibits remarkable cell imaging and mitochondrial localization ability, and can induce apoptosis by influencing the membrane potential and reactive oxygen species levels in mitochondria. Compared with phenothiazines, PCP has an excellent ability to target the mitochondria of cancer cells, and its selectivity and toxicity to tumor cells are stronger than those toward normal cells. These results demonstrated that PCP possesses strong antitumor effects with excellent selectivity, making it a promising candidate as a mitochondrial-targeted antitumor drug.
Keywords: phenothiazines; pyridinylvinylindole; mitochondria targeting; anticancer drugs; medicinal chemistry